Peningkatan Kompetensi Digital Guru PAUD Aiysiyah melalui Pelatihan AI, Canva, dan Coding untuk Mendukung Pembelajaran Mendalam: Enhancing Early Childhood Aisyiyah Teachers' Digital Competence through AI, Canva, and Coding Training to Support Deep Learning Implementation - Sistiana Windyariani; Arsyi Rizqia Amalia; Pujia Siti Balkist (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aimed to enhance teachers' digital competence through training on AI-based Canva applications and simple coding to support meaningful learning in early childhood education. The program involved 16 teachers from seven Aisyiyah kindergartens and was implemented through preparation, workshop sessions, online mentoring, and evaluation stages. A blended learning approach that combined face-to-face workshops and online support was used to ensure sustainability. Program effectiveness was evaluated using pre-test and post-test assessments as well as participant response questionnaires. The results indicated an increase in the average score from 8.25 (pre-test) to 11.63 (post-test), with an N-Gain score of 0.54 (moderate category), demonstrating that the training was moderately effective in improving teachers' understanding of AI, computational thinking, and the integration of coding in deep learning practices. Additionally, participant responses showed high satisfaction levels (82%) and improved conceptual understanding and motivation to implement AI and coding in classroom practices (84%). Overall, the program effectively strengthened teachers' digital pedagogical competence and fostered readiness for educational digital transformation in early childhood settings.